Identification of Reservoir Thickness and Estimation of Hydrocarbon Reservation used the Pre-Stack Depth Migration (PSDM) in Cikung Area - Sudra Irawan; Hanah Khoirunnisa (Politeknik Negeri Batam, 2017)
Information from the geological data shows that the Cikung field has the complex structure which is characterized by carbonate reef. Therefore, it is required in the domain depth migration (PSDM) using interval velocity model is sensitive to variations in vertical and horizontal velocity to identify the thickness of the reservoir and estimation of hydrocarbon reserves. Stages include making the depth structure maps, map making the thickness of the reservoir, and the calculation of hydrocarbon reserves. The results showed that the thickness of the reservoir in Cikung Field, estimated to range from 71 meters to 175 meters with the prospect reservoir is at a depth of 1216 meters to 1247 meters from the surface. Hydrocarbon deposits (oil) is estimated at 1,134 × 106 ???????????? or 1,311 × 108 kilo litre by the porosity of 22.6% and 70.7% water saturation.